Influence of Forest Structural Complexity and Management Intensity on Woodpecker Communities in Mediterranean Chestnut (Castanea sativa) Forests - Alexandra Demertzi; Christina Gerontidou; Nikolaos Gogolos; Anastasios Bounas (Ecologies)
Mediterranean chestnut forests represent ecologically and economically important systems that support biodiversity while providing timber, non-timber forest products, and cultural services. However, traditional management practices are undergoing substantial shifts, with potential implications for forest structure and biodiversity. This study investigates how variation in forest structure and management intensity influences woodpecker communities in chestnut-dominated forests on Mount Paiko, northern Greece. Standardized surveys were conducted at 26 sites stratified by management intensity, and structural forest characteristics such as tree diameter, basal area, and deadwood volume were quantified. Species richness, abundance, and habitat use (feeding and nesting signs) were assessed in relation to these variables. Seven woodpecker species were detected, with distinct differences in species composition across management types. Feeding activity was positively associated with mean tree diameter, while basal area showed a significant negative correlation with woodpecker diversity. Canonical correspondence analysis revealed species-specific preferences along structural gradients, highlighting the association of the Black and Lesser Spotted woodpeckers with larger-diameter trees and deadwood-rich stands. Our results underscore the role of structural heterogeneity in supporting diverse woodpecker assemblages and highlight the need to integrate biodiversity conservation into chestnut forest management, particularly through selective retention of large trees and deadwood elements.